The Relationship of Self-Efficacy Towards High Level of Thinking Ability of USK Physics Education Student in Basic Physics I Course - Nurulwati Nurulwati*; Cut Refereni Afdar; Shahruddin Zakaria; Yusrizal Yusrizal (Jurnal Pendidikan Sains Indonesia, 2022)
The high-order thinking ability of students is currently a problem that is so difficult to improve because it must be extra developed in teaching and learning activities. This can happen because students do not often improve their higher order thinking in everyday life and in the learning process. Most students tend to have difficulty solving problems when the lecturer gives problems with a higher level of difficulty than usual. The cause of this problem needs to be investigated. This study aims to determine the relationship between self-efficacy and higher-order thinking skills of students of the Department of Physics Education, FKIP USK. The approach used is a quantitative approach with a descriptive correlational type of research. The sample of this study was the 2019 USK FKIP Physics Education students which consisted of 71 students. Data collection techniques used are questionnaires and tests. Questionnaire and test data were analyzed by descriptive analysis and Product Moment correlation analysis. The results showed that self-efficacy had a relationship with higher-order thinking skills (Sig. (2-tailed) = 0.001 0.05). It is recommended that future studies use more samples so that the results of the analysis obtained will be more accurate